Antiplatelet agents’-ticagrelol and eptifibatide-safety in experimental colitis in mice - Petrovic, Stanko S.; Vasiljevska, Milijana M.; Obradovic, Slobodan D.; Tarabar, Dino K.; Doder, Radoje B.; Majstorovic, Ivana J.; Petrovic, Marijana D.; Magic, Zvonko M.; Cikota, Bojana M.; Perisic, Nenad J.; et al. (Turkish Journal of Gastroenterology, 2020)
Background/Aims: To evaluate the side effects of two antiplatelet agents - ticagrelor and eptifibatide - in mice with experimentally-induced inflammatory bowel disease. Methods and Material: This study was designed as a controlled, animal, drug safety investigation. C57Bl/6 mice were used to establish the ulcerative colitis model by exposure to dextran sulfate sodium (DSS), and divided into three experimental groups: eptifibatide-treated (150 µg/day intraperitoneally; n = 10), ticagrelol-treated (1 mg/day via gastric tube; n = 10), and DSS-control (plain drinking water; n = 10). An unmodeled non-DSS group served as the experimental control. Complete blood count was taken for all mice at baseline (day 0, treatment initiation) and after four days of treatment. On day 4, all animals were sacrificed for autopsy. The primary outcome measure was bleeding, and the secondary outcomes were change in platelet count, hemoglobin level, and hematocrit level. Results: Neither ticagrelor nor eptifibatide treatment produced a significant effect on DSS colitis mice for the safety parameters measured. Platelet count and hemoglobin and hematocrit levels were statistically similar between the three DSS groups and the non-DSS control group (P > 0.05). Autopsy found no evidence of recent bleeding in liver, spleen, central nervous system or serous cavities. Conclusion: The antiplatelet agents ticagrelor and eptifibatide were safe in DSS colitis mice, suggesting their potential in humans suffering from ulcerative colitis, and supporting future safety studies.